Damage evolution and probabilistic strain-lifetime assessment of plain and fiber-reinforced concrete under compressive fatigue loading: Dual and integral phenomenological model. (May 2022) - Blasón, S.; Fernández Canteli, A.; Poveda, E.; Ruiz, G.; Yu, R.C.; Castillo, E.
Highlights: A new model is developed to analyze and predict lifetimes of cyclic creep curves in concrete. Fatigue damage evolution of plain and fiber-reinforced concrete is described by Weibull distribution function. Sparks-Menzies equation is explained as an inherent property of normalized damage evolution. Reliable lifetime prediction is possible even from premature interruption of fatigue test. Abstract: A phenomenological approach is proposed to describe and predict the random behaviour of the total strain in plain and fiber concrete under compressive fatigue loading. Twofold viewpoints are considered in the assessment of the fatigue damage process. The first one, acknowledged as the stochastic cumulative damage evolution in terms of the number of applied cycles is represented by a sample function, physically identified with the total specimen strain caused by matrix microcracking. The second one is ascribed to the intrinsic scatter of the total lifetime referred to as the prefixed ultimate fatigue strain limit state (not necessarily failure). The sample function, once normalized to the total fatigue lifetime, is identified as a cumulative distribution function (cdf) of the generalized extreme value (GEV) family, particularly as Weibull distribution. Besides the reliable probabilistic lifetime prediction for the material under compressive fatigue, the approach allows fatigue tests to be prematurely interrupted while the remaining evolution of the ε-N curve up to failure is fully restored from the fragment recorded. In this way, a remarkable time and cost reduction of the experimental program is achieved without detriment of data reliability.